Lumbar disc degenerative disease and lumbar stenosis: a correlation between the MRI findings and disability among low back pain patients using oswestry disability index in hospital Serdang, Malaysia - Mohamed, Faridah Hanim; Saini, Suraini Mohamad; Mahmud, Rozi; Bahari, Norafida (International Journal of Research in Medical Sciences, 2024)
Background: Low back pain is a major global disability affecting all ages and nations, costing more than coronary heart disease, diabetes, alzheimer's, and renal illnesses. Research has shown no significant correlation between MRI results and patient symptoms, highlighting the need for further investigation. Methods: A retrospective descriptive and analytical cross-sectional study was done at Hospital Serdang. From January 2017 to December 2018, data was collected retrospectively. Secondary data came from eHIS, RIS, and PACS. The data collecting forms recorded age, race, gender, oswestry disability index score, disc prolapse, and AP/SCA measures. Pearson Chi-Square and Fisher's exact tests found relationships between independent categorical variables. Pearson and Spearman's correlations determined the link between two numerical variables. We compared numerical variables, one categorical variable, and two groups using an independent T-test and a Mann-Whitney U-test. We defined statistical significance as p-value <0.05. Results: This research covered 104 patients. Hospital Serdang sees more women than men aged 30-39 with low back pain. According to the Oswestry Disability Index (ODI), patients' pain levels are most concerning and standing is most irritating. It found no correlation between MRI results (disc prolapsed and lumbar stenosis) and patient impairment (ODI score). However, patient age is significantly correlated with disc prolapse. Previous research found similar results. Conclusions: The study confirms previous MRI findings that disc degeneration and lumbar stenosis do not correlate with patient impairments, but reveal a significant correlation between disc prolapse and patient age, possibly due to structural and anatomical differences.